Helmut E. Luck and history of psychology Abstract - Zeidler, Włodzisław (Studia Psychologica: Theoria et praxis, 2012)
The article presents the figure of Helmut E. Luck, well-known scientist in the world of historians of psychology. Helmut E. Luck also is well-known in Poland, as the author or the scientific editor of several books in the field of history of psychology. In the first part of the article the short presentation of his scientific career and his scientific achievements are demonstrated. The second part comprises the analysis of his opinions in the scope of social psychology. Helmut E. Luck was the one of pioneers in psychology, who paid attention to social positive phenomena or social positive behaviors. In the field of history of psychology, H.E.Luck made the contribution to methodological analysis of psychological ideas in history, preferring the model which underlines connection of psychology with culture and at the same time creates the opportunity to analysis of biographical plots. The article also shows unquestionable and unusually merits of Luck’s in popularization of knowledge about history of psychology.